An Explanatory Case Study on Teachers’ Attitudes Toward the Inclusion of Students with Special Needs in Rural Philippine Classrooms - David, Eunice F.; Baldera, Philip R.; Ruda, Icelda D.; Santos, Vivian Q.; Ampon, Mary Dean P.; Marfil, Crisaldo S.; Opiana, Maria Joan L.; Perillo, Dejy R.; Fababeir, Janine Joy A.; Fadri, Glorylyn F.; Marquez, Franklin F.; Divinagracia, Apple G.; Gadon, Jenny Vee T.; Norombaba, Teofilo R.; Castrence, Simonette A.; Chico, Ma. Teresa M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This explanatory case study examined nine elementary teachers’ attitudes toward inclusive education in Odiongan North District, Romblon, between January and June 2025. Guided by the Social Model of Disability, Contact Theory, and the Theory of Planned Behavior, the study employed semi-structured, expert-validated focus group discussions, which were thematically analyzed to reveal four interrelated themes: moral and pedagogical motivations; contextual influences; gaps in formal professional development; and lived experiences. Insights informed a seven-module Inclusive Teaching Empowerment Series (ITES) addressing legal frameworks, differentiated instruction, co-teaching, reflective practice, and digital microlearning. The study highlights the need for sustained, context-responsive capacity building, leadership support, and resource allocation in rural, multigrade settings. Recommendations include integrating ITES into DepEd Learning Action Cells and formal peer-led workshops to scale inclusive practices.